1999
DOI: 10.1046/j.1469-7580.1999.19510001.x
|View full text |Cite
|
Sign up to set email alerts
|

The topography, architecture and structure of the enteric nervous system in the jejunum and ileum of cattle

Abstract: To date, there appear to have been no detailed and clear descriptions of the nerve plexuses and their subdivisions in the intestine of cattle. In this study, the enteric nervous system in the jejunum and ileum of 12 1-y-old calves was examined using neurofilament protein and vasoactive intestinal peptide immunohistochemistry in wholemounts and paraffin sections combined with staining of paraffin and historesin sections with haematoxylin and eosin. The main organisation of the plexuses was similar to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 22 publications
2
28
0
1
Order By: Relevance
“…The general organization of sheep ENS plexuses showed both similarities and differences between large and small laboratory animals. As in cattle (Balemba et al 1999), in the sheep ileum, it was difficult to determine the boundaries of individual large ganglia that are often of variable shape with no apparent directionality; however, some elongated ganglia with the main axis perpendicular to the underlying longitudinal muscle layer and resembling those of pigs (Scheuermann et al 1986) could be seen. The main axis of the primary nerve strands is generally oriented parallel to the longitudinal muscle layer as it occurs in the pig; however, primary nerve strands without showing an apparent directionality were also found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The general organization of sheep ENS plexuses showed both similarities and differences between large and small laboratory animals. As in cattle (Balemba et al 1999), in the sheep ileum, it was difficult to determine the boundaries of individual large ganglia that are often of variable shape with no apparent directionality; however, some elongated ganglia with the main axis perpendicular to the underlying longitudinal muscle layer and resembling those of pigs (Scheuermann et al 1986) could be seen. The main axis of the primary nerve strands is generally oriented parallel to the longitudinal muscle layer as it occurs in the pig; however, primary nerve strands without showing an apparent directionality were also found.…”
Section: Discussionmentioning
confidence: 99%
“…In small animals, the SMP forms a single network embedded in the connective tissue lying between the mucosa and the circular muscle layer. In larger species such as humans, pigs, horses, cattle, and sheep, the SMP is subdivided into an external submucosal plexus (ESP) and an internal submucosal plexus (ISP) located close to the inner circular muscle layer and lamina muscularis mucosae, respectively (Timmermans et al 1992(Timmermans et al ,2001Pearson 1994;Balemba et al 1999;Chiocchetti et al 2004). Sensory neurons, motor neurons, and interneurons are organized into functional reflex circuits that make the ENS capable of integrated reflex behavior without the involvement of the central nervous system (CNS).…”
mentioning
confidence: 99%
“…However, only limited histochemical and immunocytochemical studies of the innervation of Peyer's patches in ruminants have been undertaken. In cattle, a topographic and structural study of the ENS in jejunum and ileum was performed and demonstrated overall similarities with other species (Balemba et al, 1999), although there were some differences to the reported organization in the pig (Krammer & Kühnel, 1993).Germinal centres are poorly innervated (Felten et al, 1985), and transfer of the scrapie agent from the accumulations of PrP d at these sites to nerve endings of the peripheral nervous system is therefore difficult to explain. Access to peripheral nerves is facilitated if myelination of the nerves is reduced or absent (Kimberlin et al, 1983).…”
mentioning
confidence: 99%
“…The second is the submucosal plexus, which is located in the layer of connective tissue between the mucosal epithelium and the layers of circular smooth muscle. However, there are recent views that the ENS consists of three different ganglionated plexuses, myenteric plexus, outer submucosal plexus and inner submucosal plexus [2,3]. In addition to the ganglion plexuses, in the wall of alimentary tract, there are a large number of aganglionated nervous plexuses [35,37].…”
Section: Introductionmentioning
confidence: 99%